MENJELAJAH LUKA BATIN PENDEKATAN PSIKOLOGI KONSELING TERHADAP KESENGSARAAN MAERA DALAM NOVEL ‘KRESEK HITAM’ - Rohmatin, Kartika Nur Khozaainah (Universitas Negeri Surabaya, 2024)
Emotional pain is a psychological condition that is often experienced by people who have experienced trauma or deep emotional difficulties. Maera, the main character in the novel